Rapid Prototyping of a Dammann Grating in DMD-Based Maskless Lithography - Qi Zheng; Jinyun Zhou; Qiming Chen; Liang Lei; Kunhua Wen; Yiming Hu (IEEE Photonics Journal)
Microstructures are fabricated with a fast fabrication speed, submicron-scale precision and a minimum feature size of 1.5 μm. The proposed rapid prototyping fabrication method takes advantage of the maskless lithography technique based on a digital mirror device (DMD) and photocurable resin, which has a broad range of uses in three-dimensional (3D) printing. To illustrate the feasibility of this method, a Dammann grating is fabricated. Using a series of experiments and optimized designs, we analyze the characteristics of the photocurable resin, quantify the dose modulation for lithography and redesign the mask pattern. Consequently, a Dammann grating with a 50% diffraction efficiency is successfully fabricated, which can not only guarantee the precision but also maintain the fabrication speed. This work demonstrates the potential of this method to rapidly and directly manufacture binary optical elements or structures at the nanoscale based on photocurable resin and DMD-based maskless lithography.